Front cover: Human Milk Oligosaccharides as Promising Antivirals. Issue 6 (25th March 2018) - Morozov, Vasily; Hansman, Grant; Hanisch, Franz‐Georg; Schroten, Horst; Kunz, Clemens
Abstract : Mol. Nutr. Food Res. 2018, 62, 1700679 DOI:10.1002/mnfr.201700679 Human milk oligosaccharides (HMOs), highly abundant in breast milk, have a high potential for combating viral infections. Recent HMO binding studies for rotaviruses, noroviruses, influenza viruses, and human immunodeficiency viruses are described. The preventive and therapeutic potential of HMOs are discussed, including challenges on the route from fundamental studies to clinical trials. Further details can be found in article number1700679 by Vasily Morozov, Clemens Kunz, and co‐workers.